A Analysis of the STAD Type Cooperative Learning Model in the Anime Boruto: Naruto Next Generations by Noriyuki Abe - Abdul Gania; Rani Ardesi Pratiwi; Muhammad Iqbal (Journal of Practice Learning and Educational Development, 2026)
The purpose of this study is to analyze the application of the STAD (Student Teams-Achievement Divisions) type of cooperative learning model in the anime Boruto: Naruto Next Generations. The research method uses a qualitative approach with a type of library research. Data collection was carried out using the observation and note-taking technique on dialogues and scenes that represent the five STAD syntaxes equipped with document studies on. Data analysis techniques through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study reveal: (1) The material presentation focused on building positive interdependence , such as team exercises that emphasize "one member's failure is the team's failure." in Episodes 12, 15, 37, and 38; (2) Group division in Episode 38 work is realized through dividing heterogeneous teams with collaborative tasks in the Byakuya Gang mission Episode 44; (3) Individual tests in the Chunin Exam measure individual abilities as well as group contributions in Episodes 221 and 223; (4) Assessment of individual progress in episodes 112 and 221 (5) Group awards such as awarding certificates of appreciation in Episode 179 and inauguration of chunin in Episode 227. This study offers inspiration for innovative cooperative learning strategies.